Fluid–structure‐interaction simulations of forming‐air impact thermoforming. Issue 4 (9th February 2022) - Wagner, Simon; Sheikhi, Rasoul; Kayatz, Fabian; Münsch, Manuel; Hauptmann, Marek; Delgado, Antonio
Abstract: The authors present a thermally and dynamically coupled fluid–structure‐interaction (FSI) model of a thermoforming process variant along with simulation results. By purposeful arrangement of the inlet nozzles, the process variant under consideration seeks to improve the deformation behavior of a plastic sheet made of polyvinyl chloride (PVC), ultimately leading to a more uniform wall thickness distribution. In order to capture the complex interaction between deforming sheet and turbulent flow field in the pressure box, the numerical model must realistically reproduce both fluid and solid domain and accurately handle coupling between the simulation participants. Detailed information is provided on modeling aspects of the solid and in particular of the fluid domain. Wall thickness distributions obtained from experiments for two test cases are compared to results generated using varying parametrizations of the simulation model. The results in general are in line with experimental measurements, although some peculiarities in the measured data could not be reproduced. Despite its limitations concerning accuracy and the computational cost, the holistic simulation approach using FSI appears to be a helpful tool for investigating thermoforming due to the detailed resolution of the inflation process in time and space. Abstract : Flow pattern of annular nozzle during inflation.